Proprioception and Exercises in Individuals Suffering from Osteoarthrosis of Knee Joint: A Meta Analytic Review - Naresh Bhaskar, Raj; Soumendra, Saha; Hairul Anuar, Hashim; Srilekha, Saha (2014)
Present study was done with an intention to look into the problem of osteoarthrosis (OA) with particular reference to etiological concerns and the diverse methods of therapeutic interventions introduced to OA patients, which were virtually aimed at minimization of their problems (such as pain; difficulty in movements; range of motion (ROM) and obviously the question of quality of life (QOL). In our present attempt, we wanted highlight on the methodological issues and ways to minimize the problems. We couldn’t go through in details of analyses in few of the sections, and some of the literatures were not reviewed considering the merits of introduction of medication along with the intervention techniques which have been discussed hereafter, and we beg to be excused for that. We hope discussions carried out in this literature would encourage more replicated and methodologically valid studies in this field of research.